Effect of temperature and pressure on mechanical, surface and electrochemical properties of Al-1.5Cu-5.5Zn-2.5Mg (Alumix-431). Issue 6 (20th September 2018) - Acar, Ayşe Nur; Mutlu, Rasiha Nefise; Ekşi, Abdul Kadir; Ekicibil, Ahmet; Yazıcı, Birgül
Abstract : Purpose: The purpose of this paper is to examine new alloys created from Alumix 431 powder and investigate their mechanical and electrochemical properties. Design/methodology/approach: In this study; Alumix-431 alloy samples were prepared using the powder metallurgy (P/M) method applying cold (RT) and warm (50°C and 80°C) compaction methods under pressures of 200 and 250 MPa and were sintered at 600°C in N2 (g) atmosphere. Hardness and density of the samples were measured, and corrosion properties were determined by electrochemical impedance spectroscopy charting polarization curves. Surface characterization was determined by contact angle, scanning electron microscopy/mapping, energy dispersive X-ray spectrometry and X-ray diffractometry images. Findings: Alumix-431 alloys obtained upon compaction at 250 MPa/50 °C had the highest mechanical properties and corrosion resistance and good surface properties. On the surfaces of Alumix-431 alloys, α-Al, MgZn2, Al2, CuMg, Al2, O3, Al2 MgO4 phases were recorded. Originality/value: This study aimed to construct a correlation between mechanical and electrochemical properties of the newly created alloys (prepared under special conditions).